Alpha7 Nicotinic Acetylcholine Receptor Is a Target in Pharmacology and Toxicology - Pohanka, Miroslav (Molecular Diversity Preservation International (MDPI), 2012)
Alpha7 nicotinic acetylcholine receptor (α7 nAChR) is an important part of the cholinergic nerve system in the brain. Moreover, it is associated with a cholinergic anti-inflammatory pathway in the termination of the parasympathetic nervous system. Antagonists of α7 nAChR are a wide group represented by conotoxin and bungarotoxin. Even Alzheimer’s disease drug memantine acting as an antagonist in its side pathway belongs in this group. Agonists of α7 nAChR are suitable for treatment of multiple cognitive dysfunctions such as Alzheimer’s disease or schizophrenia. Inflammation or even sepsis can be ameliorated by the agonistic acting compounds. Preparations RG3487, SEN34625/WYE-103914, SEN12333, ABT-107, Clozapine, GTS-21, CNI-1493, and AR-R17779 are representative examples of the novel compounds with affinity toward the α7 nAChR. Pharmacological, toxicological, and medicinal significance of α7 nAChR are discussed throughout this paper.